Energy flux couples sulfur isotope fractionation to proteomicand metabolite profiles in Desulfovibrio vulgaris - Leavitt, William D. (2024)
Fil: Leavitt, William D. Dartmouth College. Department of Earth Sciences, Hanover, New Hampshire; United States of America.